Karakteristik fisikokimia tepung lima varietas lokal gembili dan potensinya dalam pengembangan mi bebas gluten - Markus Jambormias; Didah Nur Faridah; Tjahja Muhandri; Febby Jeanry Polnaya (AGROINTEK, 2025)
The development of gluten-free noodles using gembili flour offers an alternative solution to reduce Indonesia's heavy reliance on wheat flour while anticipating various health issues related to gluten consumption. This research aims to identify the physicochemical characteristics of gembili flour from five local varieties and to identify the varieties with the most potential for developing gluten-free noodles. Physicochemical characterization of flour includes measuring proximate, crude fiber, and amylose levels as well as flour pasting profile. The best varieties are identified through a theoretical approach based on the physicochemical properties of flour, especially amylose content, setback (ST), and final viscosity (FV), which are used as selection indicators. Empirical proof was carried out by measuring the cooking loss (CL) of noodles to verify the theoretical approach. The physicochemical properties of flour and CL of gembili noodles are greatly influenced by differences in varieties, except for gelatinization temperature and peak time. The Fufulu, Kapok and Kapok Kayanik varieties have high values and are not significantly different in the three selection indicators. The three varieties exhibited amylose, ST, and FV levels of approximately 23%, 204.5-276.50 cP, and 724.5-1012.5 cP, respectively. GT-Biplot analysis shows that only the Kapok and Kapok Kayanik varieties are the best varieties because they have a strong and positive relative position for the three selection indicator variables and a very negative relative position in contrast to CL compared to the other three local varieties. The Kapok variety was chosen as the best variety because it is superior in terms of nutrition and availability of raw materials compared to the other four varieties. The Kapok variety has amylose content, ST, FV, and CL of 23.19±0.34 %, 276.50±3.54 cP, 1012.5±71.4 cP, and 19.78±0.66 %, respectively.